Detection of drug resistant Mycobacterium Tuberculosis strains using kit SIRE Nitratase?: a multicenter study - Miranda, Silvana Spindola de (Instituto de Tecnologia do Paran?, 2020)
Background: The Commercial Kit SIRE Nitratase? PlastLabor, is a drug susceptibility test kit used to detect Mycobacterium tuberculosis resistance to first-line TB treatment drugs. The present study aimed at evaluating its performance in a multicenter study. (2) Methods: To determine its accuracy, the proportion methods in Lowenstein Jensen medium or the BACTECTMMGITTM960 system was used as a gold standard. (3) Results: The study revealed that the respective accuracies of the kit with 190 M. tuberculosis clinical isolates, using the proportion methods in Lowenstein Jensen medium or BACTECTMMGITTM960 system as a gold standard, were 93.9% and 94.6%, 96.9% and 94.6%, 98.0% and 97.8%, and 98.0% and 98.9%, for streptomycin, isoniazid, rifampicin, and ethambutol, respectively. (4) Conclusion: Thus, the kit can rapidly screen resistance to streptomycin, isoniazid, rifampicin, and ethambutol. Additionally, it does not require sophisticated equipment; hence, it can be easily used in the laboratories of low and middle income countries.